Persepsi Siswa terhadap Office 365 sebagai Media Penilaian Hasil Belajar secara Daring - Septian Nur Ika Trisnawati; Muhammad Fajrul Fallah; Catur Budi Wibowo (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2022)
Assessment is a critical component to determine the achievement of the learning process that has been applied to students. Assessment is carried out using various methods and tools prepared by educators. During the Covid-19 situation, schools need to change their learning mode to prevent the spread of Covid-19. This research article aims to describe students’ perception of Office 365 as a medium in students' online assessment of learning outcomes during the Covid-19 pandemic. This research was conducted at SMK Muhammadiyah Delanggu using a quantitative approach to survey research design. The population of this study was 300 students. Using a significance level of 5%, a sample size of 161 students was obtained. A simple random sampling technique took samples. The results showed that the respondents gave positive responses, scoring 72.44% in the excellent category. Assessments using Office 365 are carried out objectively and according to actual data and facts because the results can be known in real-time. This study concludes that students perceived that Office 365 is effective in online learning outcomes assessment. However, it is necessary to find other alternatives that are more able to maintain the essence of the evaluation so that the principles of assessment are more applied, and the task of educators in carrying out the supervisory function is wide open.